Sleep–Wake Control of the Upper Airway by Noradrenergic Neurons, with and without Intermittent Hypoxia - Kubin, Leszek (Prog Brain Res, 2014)
Hypoglossal (XII) motoneurons innervate muscles of the tongue whose tonic and inspiratory modulated activity protects the upper airway from collapse in patients affected by the obstructive sleep apnea (OSA) syndrome. Both norepinephrine and serotonin provide wakefulness-related excitatory drives that maintain activity in XII motoneurons, with the noradrenergic system playing a particularly prominent role in rats. When noradrenergic and serotonergic drives are antagonized, no further decline of XII nerve activity occurs during pharmacologically induced rapid eye movement (REM) sleep-like state. This is the best evidence to date that, at least in this model, the entire REM sleep-related decline of upper airway muscle tone results from withdrawal of these two excitatory inputs. A major component of noradrenergic input to XII motoneurons originates from pontine noradrenergic neurons that have state-dependent patterns of activity, maximal during wakefulness, and minimal, or absent during REM sleep. Our data suggest that not all ventrolateral medullary catecholaminergic neurons follow this pattern, with adrenergic C1 neurons probably increasing their activity during REM sleep. When rats are subjected to chronic-intermittent hypoxia, noradrenergic drive to XII motoneurons is increased by mechanisms that include sprouting of noradrenergic terminals in the XII nucleus, and increased expression of α(1)-adrenoceptors; an outcome that may underlie the elevated baseline activity of upper airway muscles during wakefulness in OSA patients.